2018
DOI: 10.3390/s18113905
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Sensorized Heart Valve Prosthesis: Preliminary In Vitro Evaluation

Abstract: Background: Recent studies have shown that subclinical valve thrombosis in heart valve prosthesis (HVP) can be responsible for reduced leaflet motion detectable only by advanced imaging diagnostics. We conceived a novel sensorized HVP able to detect earlier any thrombus formation that may alter the leaflets motion using an electric impedance measurement, IntraValvular Impedance (IVI). Methods: For IVI measurement, dedicated electrodes are embedded in the structure of the HVP to generate a local electric field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Likewise, the absence of the heart valve in the numerical body model could overestimate the HCF. The detection of impedance changes due to opening or closure of the heart valves is also being used in heart valve prosthesis [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, the absence of the heart valve in the numerical body model could overestimate the HCF. The detection of impedance changes due to opening or closure of the heart valves is also being used in heart valve prosthesis [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…370 Dedicated electrodes were also embedded in the structure of the heart valve prosthesis to generate a local electric field that is altered by the valve leaflets during their cyclic opening and closure movements. 33 This can be used to measure electric impedance and detect any thrombus formation that may alter the motion of the leaflets. Preliminary results obtained using the prototype that was applied to a simplified circulatory mock loop system, built to reproduce hydrodynamic working conditions for the sensorized valve, showed that the device provided repetitive and stable impedance measurements during the normal cyclic valve opening/closure.…”
Section: Cardiovascular Implantsmentioning
confidence: 99%
“…With the global increase in the aging population, and associated trauma and disease, the use of implants is increasing, with the implant market accounting for USD 157.97 billion in 2021 (Figure ). Implants are used for mending, reconstruction, repair, and regeneration ,, of tissues (Figure ). They can also be used as stents, shunts, and tubes.…”
Section: Current Implants Problems and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While limited inroads have been made into sensor-based monitoring techniques for cardiac health (Fonseca et al, 2006;Chen et al, 2014;Hermans et al, 2018), very few developments address the needs of TAVR patients. For instance, proof-of-concept analyses of sensorized mechanical (Marcelli et al, 2018) and transcatheter (Bailoor et al, 2021b) aortic valves have been recently proposed, but these devices cannot assist patients with existing TAVs. In this investigation, we seek to develop a safe and practical valve monitoring modality which can be independently used by patients with existing and future implants.…”
Section: Introductionmentioning
confidence: 99%